2018
DOI: 10.3892/ol.2018.9593
|View full text |Cite
|
Sign up to set email alerts
|

miR‑34a inhibits esophageal squamous cell carcinoma progression via regulation of FOXM1

Abstract: Downregulation of microRNA-34a (miR-34a) has frequently been observed in esophageal squamous cell carcinoma (ESCC). However, the underlying role and molecular mechanism of miR-34a in ESCC remains largely unknown. In the current study, it was demonstrated that miR-34a was downregulated and forkhead box M1 (FOXM1), a target gene of miR-34a, was upregulated in ESCC tumor tissues. Overexpression of miR-34a decreased FOXM1 mRNA and protein expression in the ESCC cell lines tested (TE-1 and TE-8). Inhibition of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
1
5
0
Order By: Relevance
“…MMP9 is one of key member of MMPs family. Elevating MMP9 expression plays a key role in the progression of many tumors, such as bladder cancer [25], esophageal squamous cell carcinoma [26], and intrahepatic cholangiocarcinoma [27]. Our study proved that M2 macrophages can increase HCC cells invasion and migration by upregulating MMP9 expression, this conclusion was strengthened by the outcome in response to the MMP9-shRNA which could block the biochemical and cell behavior induced by M2 macrophages in the HCC tumor microenvironment.…”
Section: Discussionsupporting
confidence: 52%
“…MMP9 is one of key member of MMPs family. Elevating MMP9 expression plays a key role in the progression of many tumors, such as bladder cancer [25], esophageal squamous cell carcinoma [26], and intrahepatic cholangiocarcinoma [27]. Our study proved that M2 macrophages can increase HCC cells invasion and migration by upregulating MMP9 expression, this conclusion was strengthened by the outcome in response to the MMP9-shRNA which could block the biochemical and cell behavior induced by M2 macrophages in the HCC tumor microenvironment.…”
Section: Discussionsupporting
confidence: 52%
“…MMP-9 is one key member of the MMPs family. The progression of various types of cancer, such as bladder, breast, esophageal squamous cell carcinoma, intrahepatic cholangiocarcinoma, hepatocellular carcinoma, is driven by the up-regulation of MMP-9 [ 135 , 136 , 137 , 138 , 139 ]. MMP-9 is able to cleave extracellular matrix components such as collagen or fibronectin, as well as many other non-collagenous substrates.…”
Section: Myc–a Key Player In the Tumor Microenvironment (Tme)mentioning
confidence: 99%
“…In this regard, miRNA has been identified to be one of the key players in regulating oncogenic developments, and therefore may possibly be manipulated in order to identify effective therapeutic outcomes (17)(18)(19)(20)(21). Other studies have supported the above-mentioned suggestion, including Sun et al, who confirmed the reduced progression of DLBC post-inhibition of miR-214, which was achieved by blocking DLBC (22).…”
Section: Discussionmentioning
confidence: 92%